2012
DOI: 10.1292/jvms.11-0505
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Canine Bone Marrow Stromal Cells (BMSCs) in the Carbon Tetrachloride (CCl<sub>4</sub>) Induced Chronic Liver Dysfunction Mouse Model

Abstract: ABSTRACT.Regenerative medicine using bone marrow cells is an attractive therapy for the cure of patients with severe liver disease. Here, we show the therapeutic potential of canine bone marrow stromal cells (BMSCs) in mouse models of CCl 4 -induced chronic liver dysfunction. We used two different models for xenotransplantation, nude mice and cyclosporine A (CSA) immunosuppressed mice. Serum parameters from a standard liver panel were not improved following transplantation. However, fibrotic liver lesions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In the hepatic fibrosis model, some studies indicated that bone marrow-derived cells could decrease collagen fibers and reduce hepatic fibrosis through expression of matrix metalloproteinases (MMPs) [4,7,8]. Haraguchi et al reported that transplanted cBMSCs migrated into liver regions exhibiting severe inflammation and fibrosis, and fibrosis was significantly reduced in CCl 4 /CSA mice transplanted with canine bone marrow stromal cells (cBMSCs) [8]. Therefore, the therapeutic effects of cBMC transplantation should be evaluated in clinical canine cases or in a hepatic fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the hepatic fibrosis model, some studies indicated that bone marrow-derived cells could decrease collagen fibers and reduce hepatic fibrosis through expression of matrix metalloproteinases (MMPs) [4,7,8]. Haraguchi et al reported that transplanted cBMSCs migrated into liver regions exhibiting severe inflammation and fibrosis, and fibrosis was significantly reduced in CCl 4 /CSA mice transplanted with canine bone marrow stromal cells (cBMSCs) [8]. Therefore, the therapeutic effects of cBMC transplantation should be evaluated in clinical canine cases or in a hepatic fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that bone marrow stromal cells (BMSCs), which are one of the components of BMCs, have various therapeutic potentials such as matrix metalloproteinase activity [7]. Furthermore, xenotransplantation using canine BMSCs may be effective in resolving inflammatory fibrotic liver in CCl 4 -treated immunodeficient mice [8]. Although some reports described autologous transplantation of BMCs in liver injured models, studies demonstrating the ability of cBMCs to accumulate in the disordered liver have been limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells, which possess certain characteristics including self-renewal, proliferation, differentiation and/or secretion of bio-active cytokines, are promising tools in cell therapy [14]. The effectiveness of bone marrow or adipose tissue-derived cells in animal models of liver fibrosis and cirrhosis have been demonstrated by several groups including us [14,[15][16][17][18][19][20]. However, others have reported the lack of any changes in the extent of liver fibrosis or liver function tests following the use of BM-MSCs in the animal models of severe chronic liver injury [21].…”
Section: Introductionmentioning
confidence: 99%
“…Major part of previous reports demonstrated their routes of administration were intravenous [14,[16][17][18][19][20]. The intravenously administered cells have reported to be accumulated to the lung and then the liver with loss of administrated cell numbers [24], resulted in reduction of efficacy.…”
Section: Introductionmentioning
confidence: 99%